2008 7th International Pipeline Conference, Volume 3 2008
DOI: 10.1115/ipc2008-64078
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Propagation and Arrest in High-Pressure Gas Transmission Pipeline by Ultra High Strength Line Pipes

Abstract: The fracture arrest of high pressure gas pipelines is one of the keen subjects for application of high strength line pipes. To examine the arrestability of high strength line pipes against crack propagation, several full scale fracture propagation tests have been conducted. The fracture propagation tests of X100 or X120 under high pressure revealed that the existing models of arrest energy prediction failed to predict the arrest energies. By careful investigations of the test results, it is found that the fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The results in References [59][60][61] showed that the modified fracture curve in Eq. (16) led to improved predictions of arrest toughness for high-strength pipeline grades X100 and X120 in comparison to the predictions by the original HLP model.…”
Section: Modified Hlp Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…The results in References [59][60][61] showed that the modified fracture curve in Eq. (16) led to improved predictions of arrest toughness for high-strength pipeline grades X100 and X120 in comparison to the predictions by the original HLP model.…”
Section: Modified Hlp Modelmentioning
confidence: 97%
“…To improve the HLP model for application to high-strength pipeline grades X80 and X100, Makino et al [59][60][61] investigated the effect of pipe geometry on the prediction of arrest toughness. It was found that the accuracy of arrest toughness prediction by the HLP model depends on pipe diameter to wall thickness ratio D/t.…”
Section: Modified Hlp Modelmentioning
confidence: 99%
“…Eqns. (5), (6) and (14) show that the direct effect factor () is related to the ratio of roughness to pipe diameter (f = ε/D) and pipe diameter (D). 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of full-scale burst tests were conducted to investigate pipeline gas decompression since the 1970s [2][3][4][5][6][7][8]. However, full scale burst tests are prohibitively costly, except for major projects.…”
Section: Introductionmentioning
confidence: 99%
“…One such important factor which is receiving increasing attention 5,6 is the presence of impurities. [11][12][13][14] Based on shock tube experiments using diff erent surface roughness pipes, Botros et al 15 for example have recently shown that in the case of pressurized hydrocarbons, ignoring pipe friction may result in overestimating the decompression wave speed, with the eff ect becoming more signifi cant with increasing line pressure and reducing pipe diameter. 7,8 Th e impact of the latter on the decompression behavior of the CO 2 stream and the appropriate pipeline fracture toughness has been the subject of a number of studies.…”
Section: Introductionmentioning
confidence: 99%